1993
DOI: 10.1084/jem.177.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Human peripheral blood basophils primed by interleukin 3 (IL-3) produce IL-4 in response to immunoglobulin E receptor stimulation.

Abstract: SummaryIn contrast to most cytokines, interleukin 4 (II_,4) expression is restricted to T lymphocytes, with the exception of mast cell lines and mast cells, as more recently demonstrated in rodents. Little is known, however, about the capacity of human nonlymphoid cells to produce I1,4. In this study we show that mature human basophils are capable of expressing I1-4 and examine the regulation of I1.,4 production in comparison with the lipid mediator leukotriene C4. 11-4 was produced upon immunoglobulin E recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
185
2
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(197 citation statements)
references
References 33 publications
8
185
2
2
Order By: Relevance
“…Inhibition studies using actinomycin D indicated that both the up-and the down-regulation of cytokine expression by IL-4 is regulated at the transcriptional level. Because we did not find any IL-4 production by mast cells themselves, IL-4 that may regulate cytokine production in mast cells seems to be produced by other cells such as Th2 lymphocytes or basophils (22,30,32).…”
Section: Discussionmentioning
confidence: 90%
“…Inhibition studies using actinomycin D indicated that both the up-and the down-regulation of cytokine expression by IL-4 is regulated at the transcriptional level. Because we did not find any IL-4 production by mast cells themselves, IL-4 that may regulate cytokine production in mast cells seems to be produced by other cells such as Th2 lymphocytes or basophils (22,30,32).…”
Section: Discussionmentioning
confidence: 90%
“…However, removal of monocytes from atopic dermatitis patients" PBMC has been shown to give opposite results on IFN-'y production: in one report IFN-7 production was still low in the remaining cell population [31], while others showed that purified Tcells from atopic dermatitis patients produced even higher amounts of IFN-7 compared wilh normals [29], Possibly, Tcells are not ihe primary affected cells in atopy. Another ceil type might be a more important source of IL-4 in IgE responses, as is suggested for cells of the mast cell/basophil lineage [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is a storage amine of mast cells and basophils. The proliferation of the precursor of both cells and the production of Ig E Abs are stimulated by Th2 cytokines such as IL-4, which are secreted by stimulated mast cells and basophils (51,52). Therefore, the effects of histamine on Th1 cytokine production may function as a negative feedback on excessive Th2 response.…”
Section: Discussionmentioning
confidence: 99%